Family Matters: High School Graduation and Sibling Influence - Wall-Wieler, Elizabeth; Roos, Leslie Leon (International Journal of Population Data Science, 2017)
Introduction Educational attainment is known to be related to family size, birth order, and the educational achievement of an older sibling. Objective This study examines younger siblings in large families, exploring the extent to which each older sibling’s educational attainment is associated with attainment of the younger sibling. Methods Linkable administrative data were used to create a population-based cohort of third children in three child families born in Manitoba, Canada between April 1, 1984 and March 31, 1994, who stayed in the province until at least age 20 (n = 5,771). Logistic regression models were used to examine the relationship between the youngest siblings’ educational achievement and that of their older two siblings, adjusting for a series of confounders. Results Youngest siblings have the greatest odds of graduating from high school if both older siblings graduated. Females also had greater odds of graduating if only one of those older siblings had graduated; this did not increase the odds for males. Associations in educational attainment were stronger when siblings were born close together. For siblings born further apart, these associations were stronger if those siblings were of the same sex as the youngest sibling. Conclusions In large families, the educational attainment of each older sibling is associated with the educational attainment of the younger sibling; associations differ depending on the birth order and sex of the older siblings. Families in which older siblings do not graduate from high school may be experiencing numerous challenges. Children with older siblings who fail to graduate may benefit from additional supports to increase their likelihood of graduation.